World at work: Dental laboratory technicians - Torbica, N; Krstev, S (Occupational and environmental medicine (London, England), 2006)
Respiratory effects Dusts generated from composites and dispersed in the breathing zone show 54-70 mass per cent to be respirable. 2 The percentage of crystalline silica in the dust varies, ranging up to 30% (Institute of Occupational and Radiological Health, Belgrade, 2003, unpublished data). According to NIOSH and ACGIH, both REL and TLV for pure silica dust are 0.05 mg/m3, while in Serbia and Montenegro the MAC is 0.1 mg/m3. The dental technician's pneumoconiosis seems to be the result of the combined effects of hard metal dusts and silica particles. 3 So far, dozens of cases of pneumoconiosis have been reported. 4- 7 Interstitial inflammation and fibrosis may sometimes be associated with occupational asthma, or with rheumatoid syndrome. 8 Even the chronic beryllium disease was seen in a dental laboratory technician. 9 Main respiratory symptoms and findings among dental technicians are cough and phlegm, as well as decreased respiratory functions. 10 Allergies, asthma, dermatitis Some studies have reported that methacrylate monomers may cause a wide range of adverse health effects, such as irritation to skin, eyes, or mucous membranes, allergic dermatitis, asthma, as well as central and peripheral nervous system disorders (headache, pain in the limbs, nausea, loss of appetite, fatigue, sleep disturbances, neuropathy, loss of memory, etc).